The cholera morbo epidemic of 1884 in Elche; An element of change of society and a new category of contemporary - Mariano Monge Juárez (Universidad de Alicante, 2018)
The arrival of the cholera epidemic in Elche, a western Mediterranean city during 1884-85, produces a set of responses: Urban changes, improvements in public health, denunciation from the press, and, above all, the development of the pro-union associative movement. The objective of this article is to interpret these responses as a set of categories of change of society that function as biopolitical strategies and their analysis can constitute a model of hermeneutic for other objects of study.